TNI Soldier Desertion: The Gap of Normative Approaches and Social Reality in the Formulation of Countermeasures Policies - Haryoto, Adi; Darmawan, Didit; Hardyansah, Rommy; Rizky, Muchamad Catur; Putra, Arif Rachman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The crime of desertion is a serious violation in the military environment that has an impact on the discipline of soldiers and the effectiveness of state defense. Previous studies tend to place desertion in a purely normative juridical perspective, so it has not fully explained the relationship between legal norms and the social factors that underlie them. This study aims to analyze the crime of desertion by TNI soldiers through a juridical-empirical approach by examining legal norms as well as identifying the causative factors and law enforcement efforts. The research method uses a juridical-empirical approach with a descriptive-analytical nature, through a literature study of laws and regulations, legal literature, and military court decisions enriched with the analysis of relevant social factors. The results of the study showed that desertion was influenced by internal factors, such as family conditions, economy, intentions, age, education, and mental readiness, as well as external factors, such as understanding regulations, workload and placement, social environment, and superior-subordinate relations. Law enforcement efforts are carried out through preventive and repressive measures. Preventive efforts include attendance supervision, mental coaching, legal counseling, and strengthening internal communication, while repressive efforts are carried out through the application of military disciplinary laws and military criminal laws, including in absentia examination mechanisms. This research contributes by offering an integrative approach between juridical analysis and social factors in understanding desertion, and recommends strengthening policies based on soldiers' welfare and sustainable discipline development as a more effective countermeasure strategy.